Risk Factors for Pfannenstiel Incisional Hernia Following Cesarean Delivery and Outcomes after Laparoscopic and Open Surgical Repair - Nevin Sakoglu; Aysun Firat (IMR Press, 2024)
Background: To analyse risk factors for cesarean section (CS)-induced incisional hernia in reproductive-aged women. Outcomes of minimal invasive herniorrhaphy and open technique were presented. Methods: Records of patients with Pfannenstiel hernia between 2010 and 2022 were reviewed. Risk factors for incisional hernia were evaluated with surgical outcomes. Results: 76 patients were included. Mean age was 46 ± 8.1 years. Bulging (81.5%), pain or discomfort (57.8%) and distention (31.5%) were the most common symptoms. We combined ultrasonography (90.7%) with contrasted tomography (71%) or magnetic resonance imaging (30%) for surgical planning. Risk factors were found as multiple previous CSs, local wound complications such as seroma, hematoma or abscess, body mass index >25, smoking, pregnancy-induced diabetes mellitus, emergency CS, and inadequate surgical technique (each, p < 0.05). In open technique (51.3%), fascia was closed by polydioxanone suture, with onlay mesh fixation. In laparoscopic hernioplasty (48.6%), tacker was used for mesh reinforcement. There was no bowel injury. Early complications were seroma and infection (p < 0.01 and p < 0.05, respectively). Most significant late complication was recurrence (7.8%). Conclusions: Clinicians should be ready to encounter more reproductive aged women with incisional hernia, since worldwide CS rate continues to rise. Awareness of risk factors, imaging methods, surgical options and outcomes are of great importance.